L’intelligenza artificiale e la persona: tra dilemmi etici e necessità di regolazione giuridica - Zanichelli, Maria (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The article will focus on the need for regulation of AI from both an ethical and legal point of view. Moving from the category divide between living intelligence and the artificial version, it points out that AI is to be considered as a tool for human ends, and human being in turn is much more than an intelligent being or a goal-directed agent. In the legal domain, AI is both a new object of regulation and a new methodological resource transforming legal practice from inside. In the face of these challenges, the concept of person (“natural person” in the legal discourse) should become the core of a normative framework setting limits and goals of AI development.